Model Konseling Berbasis Nilai Serat Wedhatama Untuk Meningkatkan Grit: Kajian Paradigma Psikologi Konseling Multikultural - Santy Andrianie; Arifah Wulandari; Ulya Makhmudah (Universitas Nusantara PGRI Kediri, 2025)
Students face challenges in completing their thesis, often leading to decreased motivation and perseverance. One factor that can support academic success is grit, which refers to consistency of interest and perseverance toward long-term goals. This study aims to examine the integration of values from Serat Wedhatama with Cognitive Behavior Therapy (CBT) to strengthen students' grit in completing their thesis. The method used is a literature review, analyzing cultural values in Serat Wedhatama and CBT principles. The findings indicate that teachings in Serat Wedhatama, such as self-control, perseverance, and self-awareness, align with grit components and CBT principles. This study proposes a counseling model based on CBT, integrating local values as a strategy to enhance students' grit. This research is conceptual and requires empirical testing to assess its effectiveness in improving students' grit.